The ultimate book hugger's guide ebook - Colfer, Chris (Land of Stories., 2018)
A behind-the-scenes, comprehensive look at the #1 New York Times bestselling series. A combination travel guide, encyclopedia, and exciting fan compendium, this ultimate guidebook includes sections such as "Who's Who," "Places to Go," and "Trinkets, Treasures, and Other Things" that explore the backgrounds and histories of the many characters, places, and magic items throughout the beloved Land of Stories series. This book also includes bonus chapters, insider information about the series, and more, including sketches from the author, "Secrets from the Land of Stories," and "Chris's Top Ten Tips for Writers." Perfect for new and mega-fans alike, this full-color guidebook illustrated by series artist Brandon Dorman captures the magical ins and outs of the Land of Stories we know and love and delivers new, never-before-seen art and information sure to thrill and satisfy readers.